Depression, Anxiety and Stress Symptoms and Substance Use among Health Care Students in Turkey during the COVID-19 Pandemic - Şeyma Zehra Altunkürek; Esra Nur Demir (Ķazaķstannyṇ Klinikalyķ Medicinasy)
Aim: People of all ages worldwide have been physically and psychologically affected by the COVID-19 pandemic. University students may be more vulnerable to the psychological effects of COVID-19 as they may be prone to high levels of stress, anxiety, and depression in general. In this study, we aimed to evaluate the depression, stress and anxiety symptoms of health care students and their attitudes toward substance abuse during the COVID-19 pandemic. Materials and methods: This was a cross-sectional study involving 1126 university students. The data collection forms consisted of the Descriptive Information Form and the Depression, Anxiety and Stress Scale (DASS). T tests, one-way analysis of variance (ANOVA) and post hoc (Tukey, LSD) analyses were used to analyze the descriptive characteristics of the participants and scale scores. Results: The mean depression score was 16.280±7.942, the mean anxiety score was 17.837±8.257, and the mean stress score was 17.686±8.247. In this study, statistically significant differences were found in terms of sex, living situation, education level, income level, use of any addictive substance, use of any addictive substance by a relative, changes in substance use during the pandemic period and mean DASS subscale score. Conclusions: Relationships were found between depression, anxiety and stress symptoms and substance use in health care university students during the pandemic. To help students overcome psychological problems during difficult situations such as the COVID-19 epidemic, it may be useful for health professionals to plan projects to reduce substance addiction.